Different behaviours in the solubilization of polycyclic aromatic hydrocarbons in water induced by mixed surfactant solutions - Sales, Pablo Sebastián (2011)
Water solubility of polycyclic aromatic hydrocarbons (PAHs), viz, naphthalene and phenanthrene, in micellar solutions at 25°C was investigated, using two series of different binary mixtures of anionic and nonionic surfactants. Tween 80 and Brij-35 were used as nonionic surfactants whereas fatty acids or amphiphilic cyclodextrins (Mod-β-CD) synthesized in our laboratory were used as anionic ones. Solubilization capacity has been quantified in terms of the molar solubilization ratio and the micelle-water partition coefficient, using UV-visible spectrophotometry. Anionic surfactants exhibited less solubilization capacity than nonionics. The mixtures between Tween 80 and Mod-β-CD did not show synergism to increase the solubilization of PAHs. On the other hand, the mixtures formed by Tween 80 and fatty acids at all mole fractions studied produced higher enhancements of the solubility of naphthalene than the individual surfactants. The critical micellar concentration of the mixtures of Tween 80/sodium laurate was determined by surface tension measurements and spectrofluorimetry using pyrene as probe. The system is characterized by a negative interaction parameter (β) indicating attractive interactions between both surfactants in the range of the compositions studied.